The Influence of Empowering RT/ RW and Village Performance towards Society Service Satisfaction Using Partial Least Squares-Sem Analysis Approach - Darul Wiyono (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
Quality of public service is one of the criteria that can be used as a tool to measure the success of good governance in carrying out its duties. On the contrary, the public satisfaction with the service given by the apparatus has influenced the empowerment policy and the performance of the administrative village itself. It means that the level of community satisfaction has an impact on the empowerment of community groups and neighborhood groups (known as RT/RW) and village apparatus performance in carrying out its duties and functions in West Bandung Regency government. This research aims to determine the influence of: (1) Empowerment of RT/RW apparatus (X1), (2) Village apparatus performance (X2), (3) Satisfaction of public service (X3) on Community service satisfaction (Y). This research categorized as a descriptive research applying the explanatory survey method and structural equation model (SEM) with partial least square (PLS) alternative technique equipped Smart PLS 3.0 software to test the hypothesis. The results suggest that the empowerment of RT/RW apparatus and village apparatus performance is an important factor in the satisfaction of public services. In other words, the satisfaction of public service cannot be separated from the empowerment of RT/RW and village apparatus performances, either partially or wholly.